Rancang Bangun Vending Machine Air Minum Isi Ulang Berbasis Internet of Things - Luki Utomo; Joko Tri Susilo; Pribandono, Andrea Bakti (Techné : Jurnal Ilmiah Elektroteknika, 2025)
The design and implementation of a refill drinking water vending machine with a multi-coin acceptor method as a metal coin detector, YF-S201 water flow as a counter for the amount of flowing water, analog TDS meter and analog pH meter as a measure of drinking water quality, NodeMCU ESP32 as a data processor, communication via the internet with the Google firebase platform as an online monitoring data display and the MIT APP Invetor platform as a data display on a smartphone application, measurement data variables are: water temperature (ºC), water pH level (pH), and Total Dissolved Solid in water (ppm). The results of testing this tool show the average accuracy value of the difference in the amount of drinking water calculated with the YF-S201 water flow sensor, in the 250mL category an average accuracy of +0.107% was obtained, the 500mL category an average accuracy of -0.346% was obtained, and the 1000mL category an average accuracy of -2.28%. The measurement results of the drinking water quality monitoring system using the TDS meter V1 analog sensor and the PH-4502C pH meter sensor, obtained fairly accurate results on the TDS parameter and the pH parameter obtained less accurate results with a measurement tolerance of ±5% compared to the calibrated instrument.